Visual studio hacks - Avery, James (Hacks series., 2005)
With start-up templates for projects ranging from Windows applications to web services, and extensive help and on-line documentation, Visual Studio .NET might be mistaken for a tool for unsophisticated users. It's true that most developers soon discover that the basic operation of Visual Studio is fairly self-explanatory; less obvious are some of the suite's more advanced built-in features. Visual Studio .Net includes a wealth of little-used capabilities, is very customizable, has a complete automation model, and much more. On top of its regular feature set, there are hosts of free add-ins, ma.